The Maastrichtian–Danian transition in the northern Farafra Oasis, Western Desert (Egypt): Implications from foraminiferal paleobathymetry and paleoenvironmental reconstructions. (August 2020) - Zaky, Amr S.; Kaminski, Michael A.; Coccioni, Rodolfo; Farouk, Sherif; Khalifa, Mohamed A.; Papazzoni, Cesare A.; Abu El-Hassan, Mohamed M.; Frontalini, Fabrizio
Abstract: Two exposed sections of the Lower/Upper Maastrichtian to Danian at northern and northeastern Farafra Oasis, Western Desert (Egypt) namely, the Farafra–Ain Dalla road and the Ain Maqfi sections have been analyzed for their planktonic and benthonic foraminifera to constrain the biostratigraphy and infer the paleoenvironmental conditions. Lithostratigraphically, the successions of the present study are classified into the Khoman Chalk and the Dakhla Shale. Biostratigraphically, six planktonic foraminiferal zones; Gansserina gansseri, Racemiguembelina powelli and Plummerita reicheli of the Maastrichtian as well as the Praemurica inconstans (P1c), Praemurica uncinata (P2) and Morozovella angulata (P3a) of the Danian are recognized. A detailed quantitative benthonic foraminiferal analysis has been performed and yields a total of 172 identified benthonic foraminiferal species belonging to 62 different genera. The various foraminiferal parameters as well as cluster analysis provide good information about the paleoenvironmental conditions and sea–level fluctuations across the Maastrichtian–Danian transition. The Maastrichtian revealed outer neritic shelf with slightly shallowing conditions recorded only at the Ain Maqfi section, well oxygenated conditions with low organic matter influx coupled with sea–level rise. During the Maastrichtian–Danian transition, a paleoenvironmental shift to inner-shallow middle neritic shelf, low oxygenated conditions with moderate organic matter influx coupled with sea–level fall is interpreted. This transition is characterized by a major hiatus due to absences of Guembelitria cretacea (P0), Parvularugoglobigerina eugubina (Pα), Parasubbotina pseudobulloides (P1a) and Subbotina triloculinoides (P1b) zones and subzones. It is well marked in the field by an irregular contact and conglomeratic phosphatic dolostone bed at the Farafra-Ain Dalla road section while the disconformity surface can be detected by planktonic foraminifera in the Ain Maqfi section. The lowermost Danian is phosphatic argillaceous chalky limestone with intensive reworking. Low oxygen and/or relatively high–moderate organic matter influx within inner–middle neritic shelf paleoenvironmental conditions can be reconstructed for the lowermost Danian associated with a slight increase in sea–level during the Praemurica inconstans (P1c) zone. The uppermost Danian reflected very well oxygenated conditions and/or low organic matter influx in middle–outer neritic shelf conditions associated with sea–level rise during ages of the planktonic foraminiferal zones P2–P3a. Highlights: Foraminiferal parameters are good indicators for the paleoenvironmental conditions. The Maastrichtian revealed outer neritic shelf coupled with sea–level rise. A paleoenvironmental shift is recorded During the Maastrichtian–Danian transition. The lowermost Danian showed inner–middle neritic shelf. The uppermost Danian reflected well oxygenated in middle–outer neritic shelf.